The Relationship Between Family Stigma And Family Burden In Caring For Patients With Severe Mental Disorders In The Working Area Of Malinau Seberang Community Health Center - Siti Kholifah; Astati; Rusdi; Desy Ayu Wardani (Universitas Negeri Surabaya, 2025)
Background: People with mental disorders often face negative stigma, including that from their own families, who should serve as their primary source of support. This stigma can increase the emotional, physical, and financial burden on families and may hinder the care and recovery process of the patient. This study aims to analyze the relationship between family stigma and family burden in caring for People with Mental Disorders. Methods: The research design used was descriptive correlational. The sampling method used was total sampling, with 36 family members caring for People with Mental Disorders who met the inclusion criteria. Data were collected using questionnaires measuring family stigma and family burden, then analyzed using Fisher’s Exact Test. Results: Among the 36 respondents caring for People with Mental Disorders, 13 respondents (36.1%) reported moderate family stigma with a moderate family burden. Meanwhile, 19 respondents (52.8%) reported severe family stigma with a moderate family burden. The analysis using Fisher's Exact Test yielded a p-value of 0.040 (p < 0.05), indicating a significant relationship between family stigma and family burden in caring for People with Mental Disorders patients. Conclusion: The stigma perceived or experienced by families plays a vital role in increasing the burden of caring for People with Mental Disorders. Therefore, educational efforts and psychosocial interventions are needed to reduce stigma and strengthen support for families, to ease the burden they experience in caring for People with Mental Disorders.